Antihypertensive Activity Profile of Bangkirai Leaves (Shorea laevis Ridl.) Ethanol Extract on Angiotensin II (4ZUD) and β-Adrenergic (6PS5) Receptors - Agus, Adhe; Siswandono, Siswandono; Butar-Butar, Maria; Fernandes, Andrian; Maharani, Rizki (Media Farmasi, 2024)
Hypertensive is a cardiovascular system disorder characterized by systolic pressure ≥ 140mmHg and diastolic ≥ 90mmHg. The increase in blod pressure is due to the mechanism of angiotensin II and β-adrenergic receptors, so in developing medicine for hypertension, compounds are needed to inhibit the activation of angiotensin II to angiotensin II, as well as β-adrenergic. Kalimantan, Indonesia has a biodiversity that has the potential as medicine such as Bangkirai (Shorea laevis Ridl.). Based on previous research on secondary metabolites, various compounds have been identified that have potential as new drug candidates, for example as antihypertensive. This study aims to determine the pharmacological profile and mechanism of angiotensin I inhibition at the 4ZUD and β-adrenergic receptors inhibition at the 6PS5 receptor, from ethanol extract of bangkirai leaves by carrying out molecular docking which begins with several stages including preparation and optimization of the structure of the test compound and structure preparation of 3D receptors 4ZUD and 6PS5. To find out the correctness of the method, validation was carried out on the Olmesartan ligand compound for 4ZUD and the propranolol ligand for 6PS5. Based on research carried out on both receptors, results were obtained for the test compounds in the form of MolDockScore, the pharmacological profile of absorption, distribution, metabolism, excretion, and toxicity. MolDockScore results show that the compound Colchicine, N-desacetyl-N-[4-hydroxy-3,5-dimethoxycinnamoyl] has the lowest values, namely -146.503 at the 4ZUD receptor dan -129.718 at the 6PS5 receptor, which is close to the natural ligand value compared to other metabolite compounds. Apart from that, it also provides good results based on the pharmacological profile of the 4ZUD and 6PS5 receptors including HIA (95.73%), Caco2 (35.14nm/second), and PPB (87.67%). Negative test results are also shown in the mutagenic toxicity profile (Ames Test Method), non-mutagenic, and carcinogenic tests which include genotoxic and nongenotoxic.